Investigation of Primary Education Teacher's Attributes to Technological Pedagogical Content and Distance Education - Döner, Kübra; Kesicioglu, Oguz Serdar (Fırat Üniversitesi, 2023)
In the present study, the objective was to examine pre-service primary school teachers' technological pedagogical content knowledge and their approaches towards distance education. In this study, which is a survey model, the sample consists of 423 pre-service teachers studying at Faculty of Education, Department of Primary Education, Department of Classroom Education in the 2021-2022 academic year. "Personal Information Form" and "Technological Pedagogical Content Knowledge Scale" and "Attitude Towards Distance Education Scale" have been included as data collection instruments in the study. The responses of the pre-service teachers to the survey scales have been gathered in an online environment. The findings of the study revealed that the technological pedagogical content knowledge of pre-service primary school teachers did not show a statistically significant difference in terms of gender and grade level variables. On the other hand, statistically significant differentiation has been encountered in the university of study, having a personal computer and the dimentions of the district of residence. While gender, university, and grade level did not show a statistically significant difference in the comparison of pre-service teachers' attitudes towards distance education, there was a statistically significant difference in terms of having a personal computer and district of residence.

Bu çalışmanın amacı, sınıf öğretmenliği öğretmen adaylarının teknolojik pedagojik içerik bilgileri ve uzaktan eğitime yönelik tutumlarını incelemektir. Tarama modelinde olan çalışmanın örneklemini 2021-2022 eğitim-öğretim yılı Eğitim Fakültesi Temel Eğitim Bölümü Sınıf Eğitimi Ana Bilim Dalı’nda öğrenim görmekte olan 423 sınıf öğretmen adayı oluşturmaktadır. Çalışmada veri toplama aracı olarak “Kişisel Bilgi Formu” ve “Teknolojik Pedagojik İçerik Bilgisi Ölçeği” ile “Uzaktan Eğitime Yönelik Tutum Ölçeği” kullanılmıştır. Öğretmen adaylarının ölçeklere verdiği cevaplar çevrim içi ortamda toplanmıştır. Çalışma sonucunda sınıf öğretmeni adaylarının teknolojik pedagojik içerik bilgilerinin cinsiyet ve sınıf düzeyi değişkenleri bakımından istatistiksel olarak anlamlı bir farklılık olduğunu göstermediği belirlenmiştir. Öğrenim görülen üniversitede, kişisel bilgisayara sahip olmada ve yaşadığı bölge boyutlarında ise istatistiksel olarak anlamlı farklılaşma olduğu görülmüştür. Sınıf öğretmen adaylarının uzaktan eğitime yönelik tutumlarının karşılaştırılmasında ise cinsiyet, öğrenim görülen üniversite ve sınıf düzeyi istatistiksel olarak anlamlı bir farklılaşma olduğu görülmezken kişisel bilgisayara sahip olma ve yaşadığı bölge bakımından istatistiksel olarak anlamlı farklılaşma olduğu sonucuna ulaşılmıştır.
SINIF ÖĞRETMENİ ADAYLARININ TEKNOLOJİK PEDAGOJİK İÇERİK BİLGİLERİ VE UZAKTAN EĞİTİME İLİŞKİN TUTUMLARININ İNCELENMESİ